Exploring the Potent Anticancer Activity of Essential Oils and Their Bioactive Compounds: Mechanisms and Prospects for Future Cancer Therapy - Fatouma Mohamed Abdoul-Latif; Ayoub Ainane; Ibrahim Houmed Aboubaker; Jalludin Mohamed; Tarik Ainane (MDPI AG, 2023)
Cancer is one of the leading causes of death worldwide, affecting millions of people each year. Fortunately, the last decades have been marked by considerable advances in the field of cancer therapy. Researchers have discovered many natural substances, some of which are isolated from plants that have promising anti-tumor activity. Among these, essential oils (EOs) and their constituents have been widely studied and shown potent anticancer activities, both in vitro and in vivo. However, despite the promising results, the precise mechanisms of action of EOs and their bioactive compounds are still poorly understood. Further research is needed to better understand these mechanisms, as well as their effectiveness and safety in use. Furthermore, the use of EOs as anticancer drugs is complex, as it requires absolute pharmacodynamic specificity and selectivity, as well as an appropriate formulation for effective administration. In this study, we present a synthesis of recent work on the mechanisms of anticancer action of EOs and their bioactive compounds, examining the results of various in vitro and in vivo studies. We also review future research prospects in this exciting field, as well as potential implications for the development of new cancer drugs.